2019
DOI: 10.4102/sajbm.v50i1.398
|View full text |Cite
|
Sign up to set email alerts
|

Business coaching: A hen with ducklings

Abstract: Background: Globally, business coaching is an unregulated industry that is not yet considered a profession. In South Africa, two of the regulatory bodies, namely Coaches and Mentors of South Africa and the Institute of Management Consultants and Master Coaches of South Africa, were recognised as professional non-statutory bodies in 2015. Aim:The purpose of this study is to inquire into how business coaching is currently being practised in South Africa from a practitioner's perspective.Setting: At this key poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(32 reference statements)
0
7
1
Order By: Relevance
“…This potentially points to coaches in Africa using less-sophisticated approaches when compared with, for example, coaches in Europe where only 23% reported to use the Behavioural or Goal-focussed or GROW (Passmore et al, 2017). Our result also differs from a South African study (Schutte, 2019) that found South African coaches to predominantly use their own coaching model and a positive psychology approach.…”
Section: Coaching Approaches Usedcontrasting
confidence: 99%
See 2 more Smart Citations
“…This potentially points to coaches in Africa using less-sophisticated approaches when compared with, for example, coaches in Europe where only 23% reported to use the Behavioural or Goal-focussed or GROW (Passmore et al, 2017). Our result also differs from a South African study (Schutte, 2019) that found South African coaches to predominantly use their own coaching model and a positive psychology approach.…”
Section: Coaching Approaches Usedcontrasting
confidence: 99%
“…In a South African study (n = 148), 63% of participants indicated that they used their own coaching model, 59% used a positive psychology approach and 40% of coaches used a narrative approach (participants were allowed to select more than one option) (Schutte, 2019). No research could be found on Pan-African coaching approaches, an aspect addressed in the present study.…”
Section: Coaching Approachesmentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, the theoretical grounding of the current study in the ecosystems theory lends higher power of explanation and prediction. The proliferation of coaching literature by not using theory does not contribute to professionalizing coaching as an industry (Schutte, 2019). Therefore, the current study advances the growing research on systemic coaching for exploring ways of higher coaching effectiveness.…”
Section: Discussionmentioning
confidence: 94%
“…Serenko and Bontis (2013, p. 138) contend that for any discipline to be acknowledged as a profession should demonstrate two attributes: it should provide a theoretical, conceptual and methodological foundation to research and practice and the discipline should improve "the state of practice, ensure practical application of academic findings and increase the quality of life." Sperry (2013) doubts if coaching meets with the two criteria for it to be recognized as a profession, while Schutte (2019) expresses concern that coaching is not considered a profession as it is an unregulated industry. Hence, contribution toward theoretical grounding of coaching and higher effectiveness will advance professionalizing the coaching industryan attempt this study makes and contributes by employing ecosystem theory and a systemic approach to coaching that predicts higher coaching effectiveness.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%